The relationship between psychological resilience, perceived social support, acceptance of illness and mindfulness in patients with hepatolenticular degeneration - Tiemei Wang; Nianwei Wu; Senlin Wang; Yanjun Liu (Scientific Reports)
Abstract To investigates the current status of mindfulness in patients with Wilson’s disease (WD) and to explore the effects of psychological resilience, perceived social support, and acceptance of illness on their mindfulness. By using the convenient sampling method, 136 patients with WD were selected from May 2019 to January 2023 in 12 tertiary hospitals in Chengdu. General information questionnaire, five facet mindfulness scale, resilience scale, acceptance of illness and perceived social support scale were used to conduct the investigation. Structural equation model was used to analyze the data. The score of mindfulness of patients with WD was (128.63 ± 22.62), and there were statistically significant differences in different courses of disease, clinical classification, and hospitalization times (P < 0.05). Perceived social support (β = 0.18, P < 0.01) and psychological resilience (β = 0.36, P < 0.05) directly affected mindfulness, perceived social support (β = 0.21, P < 0.01), and acceptance of illness (β = 0.11, P < 0.05) indirectly affected mindfulness through psychological resilience. Patients with WD have moderate levels of mindfulness, psychological resilience, perceived social support and acceptance of illness directly or indirectly affect their mindfulness. Nursing staff can help patients improve their mental defense ability, actively seek more social support, dialectical view, and accept the disease to improve their level of mindfulness to promote physical and mental health.